An inverse uniqueness on the index of refraction with a transition region. Issue 3 (3rd March 2016) - Chen, Lung-Hui
Abstract : The research focuses on an inverse eigenvalue problem in an interior transmission phenomenon. There is an asymptotic structure on the eigenvalues. Given a sufficient quantity of transmission eigenvalues, we prove an uniqueness on the index of refraction in some inhomogeneous medium as an uniqueness problem in entire function theory. Interior transmission eigenvalues are intersection points of two entire functions.